Soluble epoxide hydrolase deficiency or inhibition enhances murine hypoxic pulmonary vasoconstriction after lipopolysaccharide challenge - Wepler, Martin (Am J Physiol Lung Cell Mol Physiol, 2016)
Hypoxic pulmonary vasoconstriction (HPV) is the response of the pulmonary vasculature to low levels of alveolar oxygen. HPV improves systemic arterial oxygenation by matching pulmonary perfusion to ventilation during alveolar hypoxia and is impaired in lung diseases such as the acute respiratory distress syndrome (ARDS) and in experimental models of endotoxemia. Epoxyeicosatrienoic acids (EETs) are pulmonary vasoconstrictors, which are metabolized to less vasoactive dihydroxyeicosatrienoic acids (DHETs) by soluble epoxide hydrolase (sEH). We hypothesized that pharmacological inhibition or a congenital deficiency of sEH in mice would reduce the metabolism of EETs and enhance HPV in mice after challenge with lipopolysaccharide (LPS). HPV was assessed 22 h after intravenous injection of LPS by measuring the percentage increase in the pulmonary vascular resistance of the left lung induced by left mainstem bronchial occlusion (LMBO). After LPS challenge, HPV was impaired in sEH(+/+), but not in sEH(−/−) mice or in sEH(+/+) mice treated acutely with a sEH inhibitor. Deficiency or pharmacological inhibition of sEH protected mice from the LPS-induced decrease in systemic arterial oxygen concentration (Pa(O(2))) during LMBO. In the lungs of sEH(−/−) mice, the LPS-induced increase in DHETs and cytokines was attenuated. Deficiency or pharmacological inhibition of sEH protects mice from LPS-induced impairment of HPV and improves the Pa(O(2)) after LMBO. After LPS challenge, lung EET degradation and cytokine expression were reduced in sEH(−/−) mice. Inhibition of sEH might prove to be an effective treatment for ventilation-perfusion mismatch in lung diseases such as ARDS.